Brown queer compositionistas and the reflective practice of automythnography. Issue 4 (2nd October 2017) - Inayatulla, Shereen
ABSTRACT: Autoethnographic self-reflection is a strategy for teachers to examine their pedagogies and academic workspaces at large. In the process of moving from teaching composition at an institution in the Midwest to one in Southeast Queens, this author describes significant shifts in how she perceived herself as a Brown queer pedagogue. In order to analyze these shifts in ways that advance her pedagogical praxis, the author evaluates the research tools available to her and offers a hybrid method for reflection, which she calls "vulnerable automythnography." Applying this reflective practice to a specific classroom occurrence, the author considers some ways in which vulnerable automythnography offers underrepresented teachers and students an opportunity to examine the aggressions Black, Brown, and queer bodies face in academic settings. She posits this method of reflection as a tool for savvy resistance and intervention.